Evolving Nationalism : Homeland, Identity, and Religion in Israel, 1925-2005 - Shelef, Nadav G. (Book collections on Project MUSE., 2018)
Evolving Nationalism examines how the idea of Israel as a nation-state has developed within Zionist and Israeli discourse over the past eight decades. Nadav G. Shelef focuses on the changing ways in which the main nationalist movements answered three distinct questions in their private and public ideological articulations between 1925 and 2005: Where is the "Land of Israel"? Who ought to be Israeli? What should the Zionist national mission be?Framed within broader debates about how and why changes in foundational definitions of the nation occur, Shelef's analysis centers on the mechanisms of ideological change and then subjects them to empirical scrutiny. He thus moves beyond the common but problematic assumptions that such transformations must be either a rare, rational adaptation to traumatic shock or a relatively constant product of manipulation by power-hungry elites. He finds that nationalist movements, including radical and religious fundamentalist ones, can and do change cardinal components of their ideological beliefs in both moderating and radicalizing directions.These changes have more to do with the unguided consequences of engagement in day-to-day politics than with strategic reaction to new realities, the use of force, or the changing incentives of leaders. Engaging with some of the most contentious debates about the nature of Israeli nationalism and the geographic, religious, and ethnic definition of the state of Israel, Shelef has made signal contributions to our understanding of Middle East politics and of the ideological underpinnings of nationalism itself.